Ox-LDL induces a non-inflammatory response enriched for coronary artery disease risk in human endothelial cells - Jiahao Jiang; Thomas K. Hiron; Anil Chalisey; Yashaswat Malhotra; Thomas Agbaedeng; Chris A. O’Callaghan (Scientific Reports)
Abstract Oxidised low-density lipoprotein cholesterol (ox-LDL) is critical in the initiation and progression of atherosclerosis. While excessive atherogenic lipids in the arterial intima can trigger endothelial dysfunction in advanced lesions, the response of endothelial cells to ox-LDL in the early stages of atherogenesis remains unclear. Here, we conducted a comprehensive, genome-wide multi-omics characterisation of the cellular response to ox-LDL in primary human aortic endothelial cells (HAECs). Our results reveal that the exposure of HAECs to ox-LDL leads to pathogenic changes in metabolism, transcriptome and epigenome, but in the absence of a typical inflammatory endothelial phenotype. An integrative analysis implicates the role of AP-1, NFE-2 and CEBP transcription factors in regulating ox-LDL-induced transcription. We further demonstrate that ox-LDL activates endothelial cell migration through the epigenomic rewiring of transcription factor binding. Notably, these ox-LDL-induced dynamic binding sites are enriched for the genetic risk of coronary artery disease, enabling the discovery of the gene-environment interaction of rs62172376 and ox-LDL at the CALCRL/TFPI locus. Collectively, our findings provide an unbiased understanding of the transcriptional regulation in endothelial cells in response to ox-LDL, together with its interaction with the genetic element of coronary artery disease.